MONITORING OF DEVELOPMENT OF THE DOMESTIC MARKET OF AIR TRANSPORT AT THE PRESENT STAGE - A. Zinchenko (Вестник университета)
Article is devoted to a research of tendencies of development of the domestic market of air transportation and aircrafts for a long-term outlook. On the basis of application of economic methods of the comparative, index and horizontal analysis the forecast of passenger and freight transportation is submitted. The offered forecast is constructed taking into account the existing tendencies of development of the world market of air transportation. It is shown that growth of volume of passenger and transport traffic is provided not only due to intensity of operation, but also due to accumulation of number of the park of aircrafts and its carrying capacities.